2014
DOI: 10.1016/j.neuroimage.2014.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable neural representations of wrist motor coordinate frames in human motor cortices

Abstract: There is a growing interest in how the brain transforms body part positioning in the extrinsic environment into an intrinsic coordinate frame during motor control. To explore the human brain areas representing intrinsic and extrinsic coordinate frames, this fMRI study examined neural representation of motor cortices while human participants performed isometric wrist flexions and extensions in different forearm postures, thereby applying the same wrist actions (representing the intrinsic coordinate frame) to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 51 publications
5
23
0
Order By: Relevance
“…4 ) showed that the hand knob and M1 were the main contributive areas for controlling finger movement in the intrinsic coordinate frame, while PMd and PMv were the main contributors for movement direction towards the target in the extrinsic coordinate frame, depending on their timing in transition from motor planning to execution. The differences in mapping were consistent with existing studies on non-human primates and humans 24 , 27 , 28 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…4 ) showed that the hand knob and M1 were the main contributive areas for controlling finger movement in the intrinsic coordinate frame, while PMd and PMv were the main contributors for movement direction towards the target in the extrinsic coordinate frame, depending on their timing in transition from motor planning to execution. The differences in mapping were consistent with existing studies on non-human primates and humans 24 , 27 , 28 .…”
Section: Discussionsupporting
confidence: 89%
“…We compared topological maps for the Int-label and Ext-label decoders to determine if they used signals from areas physiologically relevant to the 8 intrinsic coordinate movements and 8 extrinsic coordinate movements for each motor control phase, motor planning and motor execution. Since we previously demonstrated neural representation of the two motor coordinate frames using fMRI 24 , and the results are consistent with existing findings using non-human primates 27 29 , 54 , 55 , the current study also targeted the same 5 ROIs: M1, PMd, PMv, SMA, and pre-SMA. The 5 ROIs were defined based on the Human Motor Area Template (HMAT) 56 .…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations